Effectiveness of Advanced Technology and Engineering in Biology Learning Model for SDGs in Changing Student’s Conservation Perceptions about Phytoplankton Group - Abdillah, Ghauts Mannah Aji; Suwono, Hadi; Fachrunnisa, Rifka (BIOEDUKASI, 2024)
Indonesia has a very diverse biodiversity, but its people still have a low awareness of conservation. The purpose of this study is to determine the effectiveness of applying advanced technology and engineering in biology learning models for SDGs to change students' perceptions of conservation. This research is applied to the material of biodiversity and environmental change. This study’s sample are 10th-grade students of State Senior High School Turen, which were taken using a purposive sampling technique. Methods of data collection using one-group pretest-posttest design, questionnaires, and reflective essays. Data analysis used the Pearson Product Moment validity test, Kolmogorov-Smirnov normality test, homogeneity test, N-Gain score for learning effectiveness, Likert scale descriptive analysis for analyzing questionnaires, and thematic analysis for analyzing reflective essays. This study’s results are the effectiveness of applying this learning model on biodiversity material and environmental change material, both of them are classified as quite effective in changing students' perceptions of conservation. Previously student’s conversation awareness is classified as strong, and now become to very strong. The reflective essay’s result showed this learning provides new insights regarding phytoplankton which makes students aware of the existence of these phytoplankton so that they have an interest in doing conservation.